Effect Of Work Facilities And Motivation On Employee Satisfaction Of Pt. Pasar Swalayan Maju Bersama Glugur - Leony Hoki; Cindy Gotama (Jurnal Mantik, 2022)
This study aims to determine the effect provided by the facilities and work motivation on job satisfaction of employees of PT. Pasar Swalayan Maju Bersama Glugur. The instrument to be used is a questionnaire which has been tested for validity and reliability first. Data analysis techniques used in the form of multiple linear regression analysis, partial test, simultaneous, and coefficient of determination. The results of the study show that partially the variables of facilities and work motivation have a significant influence on job satisfaction of employees of PT. Pasar Swalayan Maju Bersama Glugur. The results of the study also found that simultaneously the variables of facilities and work motivation had a significant influence on job satisfaction of employees of PT. Pasar Swalayan Maju Bersama Glugur.